Pengaruh Bahan Baku dan Teknologi Terhadap Hasil Produksi UMKM Opak di Desa Pegajahan Kecamatan Pegajahan Kabupaten Serdang Bedagai - Muhammad Fadlan Hidayat; Hendra Saputra (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2023)
This study examines the effect of raw materials and technology on the production results of "opak" Micro, Small and Medium Enterprises (UMKM) in Pegajahan Village, Pegajahan District, Serdang Bedagai Regency. Using a quantitative approach, this research was conducted with a total sampling of 60 opak UMKM owners. Data collection used a Likert scale questionnaire, analyzed through multiple linear regression with SPSS 26.0. The results reveal a significant positive effect of Raw Materials on Production Results, while Technology has no effect on production results. Regression analysis shows that Raw Materials contribute 17.4% and Technology 4% to Production Results. Furthermore, based on the results of the study, it shows that the raw material and technology variables simultaneously have a positive and significant effect on production results. The coefficient of determination test shows a value of 0.241, which means that the effect of raw materials and technology on production results is 24.1% while the rest is influenced by other variables. outside of this research.